Pembelajaran Mengenal Rambu-Rambu Lalu Lintas Dengan Mengaplikasikan Model Instructional Games - Nani Agustina - AMIK BSI Jakarta (Indonesian Journal on Software Engineering (IJSE), 2017)
Abstract - The development of technology is closely related to education. Utilization of computer technology by applying learning using flash media instructional games is very useful in terms of helping the delivery of material. With a learning system that only the delivery of theory and the direction of the teacher's explanation many students feel bored with what is delivered and do not really understand what to convey by the teacher. Model Instructional Games here students are invited to understand learning to know the signs of traffic with the model of games by following the rules that have been established, with this method students become unsaturated in doing learning and with this media so challenged students to keep trying in order to achieve goals which is desired, by continuously trying to repeat the students will be recorded material to be conveyed. The development of instructional media with Instructional Games media applied at SDN Jatibening III Bekasi, based on the validation of experts average rating 3.59 and based on material experts 3.67. For the assessment of success is also assessed based on students with a level of 92.31% completeness, with an average percentage of 79.95%, of these results provide feasibility as a medium of learning.Keyword: Traffic Signs, Instructionn Games Abstract  –  Perkembangan teknologi sangat erat kaitannya dengan dunia pendidikan. Pemanfaatan teknologi komputer dengan menerapkan pembelajaran menggunakan media flash model instructional games sangat berguna dalam hal membantu penyampaian materi. Dengan sistem pembelajaran yang hanya penyampaian secara teori dan penjelasan searah dari guru banyak siswa merasa jenuh dengan apa yang disampaikan dan tidak memahami benar apa yang ingin disampaikan oleh guru. Model Instructional Games disini siswa diajak untuk memahami pembelajaran mengenal rambu-rambu lalulintas dengan model games dengan mengikuti aturan-aturan yang telah ditetapkan, dengan metode ini siswa menjadi tidak jenuh dalam melakukan pembelajaran dan dengan media ini siswa jadi tertantang untuk terus mencoba agar bisa mencapai tujuan yang diinginkan, dengan terus mencoba berulang-ulang siswa akan terekam materi yang ingin disampaikan. Pengembangan media pembelajaran dengan media Instructional games yang diterapkan pada SDN Jatibening III Bekasi, berdasarkan validasi para ahli rata-rata penilaian 3,59 dan berdasarkan ahli materi sebesar 3,67. Untuk penilaian keberhasilan juga menilai berdasarkan siswa dengan tingkat ketuntasan 92,31%, dengan presentase rata-rata sebanyak 79,95% , dari hasil tersebut memberikan kelayakan sebagai media pembelajaran.Keyword: Rambu-rambu lalulintas, Instructionn Games